2019
DOI: 10.2147/ott.s184235
|View full text |Cite
|
Sign up to set email alerts
|

<p>miRNA-101-5p inhibits the growth and aggressiveness of NSCLC cells through targeting CXCL6</p>

Abstract: BackgroundThe purpose of this study is to explore the potential biological roles of miR-101-5p in the progression of non-small-cell lung carcinoma (NSCLC).MethodsThe levels of miR-101-5p and chemokine (C-X-C motif) ligand 6 (CXCL6) in NSCLC tissues and cells were detected using the quantitative real-time PCR (qRT-PCR) assay. Proliferation, colony formation, migration and invasion assays were conducted using miR-101-5p-transfected NSCLC cells in vitro. The expression of CXCL6 was measured using immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Interaction between hsa_circ_0007364 and miR-101-5p was confirmed using a dual-luciferase reporter and RIP assay. MiR-101-5p delays tumor growth in various cancers, including liver cancer, lung cancer and clear cell renal cell carcinoma [11][12][13]. In agreement with these reports, we showed that miR-101-5p expression is suppressed in CC tissues, and that miR-101-5p suppression abated the suppression of the proliferative and invasion ability of CC cells caused by hsa_-circ_0007364 silencing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interaction between hsa_circ_0007364 and miR-101-5p was confirmed using a dual-luciferase reporter and RIP assay. MiR-101-5p delays tumor growth in various cancers, including liver cancer, lung cancer and clear cell renal cell carcinoma [11][12][13]. In agreement with these reports, we showed that miR-101-5p expression is suppressed in CC tissues, and that miR-101-5p suppression abated the suppression of the proliferative and invasion ability of CC cells caused by hsa_-circ_0007364 silencing.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Yamada et al [ 11 ] showed that miR‐101‐5p acted as an antitumor miRNA in clear cell renal cell carcinoma cells. Chen et al [ 12 ] revealed that miRNA-101-5p suppressed lung cancer cell growth and aggressiveness via targeting CXCL6. Furthermore, Shen et al [ 13 ] found that miRNA-101-5p reduced CC cells’ proliferation and invasion through suppressing CXCL6.…”
Section: Introductionmentioning
confidence: 99%
“…In a few reports, miR‐101‐5p expression was found to be downregulated. miR‐101‐5p was shown to inhibit cell aggressiveness through targeting of C‐X‐C motif chemokine ligand 6 ( CXCL6 ) in cervical cancer and nonsmall‐cell lung carcinoma . To our knowledge, the present study is the first report to show the antitumor functions of miR‐101‐5p in ccRCC.…”
Section: Discussionmentioning
confidence: 65%
“…Compared with reports of miR-101-3p, few studies have reported the tumor-suppressive functions of miR-101-5p and its target molecules in cancer cells. More recently, downregulation of miR-101-5p was reported in non-small cell lung carcinoma tissues compared with that in normal tissues (Chen et al, 2019). Overexpression of miR-101-5p was shown to suppress the aggressive phenotypes of cancer cells (in vitro) and pulmonary metastasis (in vivo) by regulating CXCL6 (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%